Covid 19: How Is the Ability of Local Governments to Deal with It? - Nia Audia; Roni Ekha Putera; Desna Aromatica (Publik : (Jurnal Ilmu Administrasi), 2021)
Countermeasures to minimize the spread of Covid-19 are still being carried out. The city of Padang has reduced the rate of the space of Covid-19 when implementing the Large-Scale Social Restriction policy. However, the spike in Covid-19 cases occurred again when the New Normal policy began to be implemented in the city of Padang. The purpose of this study is to explain the ability of local governments in dealing with Covid-19. The research method in data collection is qualitative through interviews and documentation. The results of this study are that the Padang City Covid-19 Handling Task Force as a local government agency for the Covid-19 response has played a good role in overcoming Covid-19 in Padang City. However, several things need to be maximized related to the capacity of the local government in Padang City. First, in the Human Resources variable, regarding the resources of health workers and health service facilities for handling health for Covid-19 survivors at the Padang City regional hospital, it still needs to be improved. Second, on the technical variables, namely Covid-19 logistics, there are still some Covid-19 survivors who do not receive logistical assistance when self-isolating Covid-19 at home, besides that the Covid-19 Handling Task Force also still needs to maximize its coordination in conveying information. The latest news regarding the development of Covid-19 to the public. Therefore, to suppress the rate of growth of Covid-19, the ability of local governments is urgently needed